Hubungan Antara Puasa Senin Kamis Dalam Mengontrol Kesehatan Mental - Erni Tresna Apriyani; Fildzah Farahiyah; Okti Hazrati; Qurrotul Aeni; Hisny Fajrussalam (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Fasting Monday and Thursday is a sunnah worship. Fasting can maintain a person's health. The research aims to provide an understanding of the impact of Monday and Thursday fasting on mental health. The research results show that fasting Monday and Thursday has an effect on mental health. This research was prepared using a qualitative method approach, namely document study research.